How ESG Disclosure Affects Firm Value: The Mediating Role of Tax Avoidance - Rela Sari; Tabah Rizki; Alya Melinda Putri; Nilam Kesuma; Rochmawati Daud; Atiqa Malik (Universitas Negeri Malang, 2026)
This study aims to examine the effect of environmental, social, and governance (ESG) disclosure on firm value with tax avoidance as a mediating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with a Random Effect Model (REM) panel data regression method on 84 observations collected during the 2022-2024 period. The results show that ESG disclosure has a significant negative effect on tax avoidance, indicating that increased transparency and sustainability responsibility can reduce corporate tax avoidance practices. Additionally, ESG disclosure has a significant positive effect on firm value, while tax avoidance has a significant negative effect on firm value. Furthermore, tax avoidance was found to partially mediate the relationship between ESG disclosure and firm value, confirming that taxation policy is one of the key mechanisms in the process of creating firm value. These findings confirm that ESG disclosure not only serves as an instrument of legitimacy, but also as an effective corporate strategy in increasing firm value through risk management, transparency enhancement, and strengthening stakeholder trust. Practically, the results of this study have implications for company management to integrate ESG strategies with ethical tax policies, as well as for investors to make the quality of ESG disclosure and the level of tax compliance key indicators in assessing the prospects and sustainability of firm value in the future.